EVALUASI PENERIMAAN PAJAK DAERAH SEBAGAI ELEMEN PENDAPATAN ASLI DAERAH KABUPATEN KONAWE - Tamburaka, Sulvariany; Hasbuddin, Hasbuddin; Pina, Adol (JURNAL AKUNTANSI DAN KEUANGAN, 2018)
ABSTRACT The aim of this research is to find the effectiveness and contribution of the local tax to PAD in Konawe. The type of data used is quantitative data and qualitative data. Technical aggregate of the data used in interview, documentation, adn study literature. The research method used is descriptive method. The result of this research show that revenue from 2013 amount of 118%, while in 2014 and 2015 amount of 109%. Therefore, averaged of revenue during in 2013-2015 amount of 112%. Thus based on the criteria of effectiveness that has been determined the local tax revenue has been very effective, because the target achieved more than 100%. While the local tax contribution in increasing the original revenue of districts in Konawe in 2013-2015 an average of 25%. Based on the criteria of contribution that have been determined quite contribute, which is caused by local tax revenue from year to year continue to increase. Keywords: Evaluation, Local Tax Revenue, Local Revenue.